2002
DOI: 10.1007/s00792-002-0275-6
|View full text |Cite
|
Sign up to set email alerts
|

The search for traces of life: the protective effect of salt on biological macromolecules

Abstract: Trapping malate dehydrogenase from the extremely halophilic archaeon Haloarcula marismortui in "dry" salt crystals protects the enzyme against thermal denaturation. Similar protection was not observed for the homologous mesophilic enzyme. In the case of transfer RNA molecules, high salt concentration plays a protective role against thermal degradation allowing activity to be recovered. The results are discussed in the context of exploring the fate of cell-free biological macromolecules in the environment and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Moreover, several studies have reported the existence of viable cells from salt deposits hundreds of million years old (37-39). We have shown that halophilic proteins or RNA embedded in salt crystals were protected from heat denaturation (40). Hypersaline conditions exist in other planets of our solar system.…”
Section: Halophiles: Model Organisms In Exobiology and Environmental mentioning
confidence: 96%
“…Moreover, several studies have reported the existence of viable cells from salt deposits hundreds of million years old (37-39). We have shown that halophilic proteins or RNA embedded in salt crystals were protected from heat denaturation (40). Hypersaline conditions exist in other planets of our solar system.…”
Section: Halophiles: Model Organisms In Exobiology and Environmental mentioning
confidence: 96%
“…They can accumulate rapidly, given a continuous flux of water, so may entrap surface-dwelling organisms. Gypsum and halite crusts in particular seal organic remain effectively (Tehei et al 2002).…”
Section: Diversity Of Crustsmentioning
confidence: 99%
“…Any extrapolations from results obtained in the laboratory to what may have occurred 4 billion years ago are tenuous. As a result we have to study the stability of all components in extreme conditions, that is the behaviour of monomers and macromolecules of life at high and cold temperatures (Schwartzman and Lineweaver, 2004;Vergne et al, 2006), with and without salt (Tehei et al, 2002), at low and high pH (Ku¨hne and Joyce, 2003), at low and high pressure (Tobe´et al, 2005;Di Giulio, 2005), in different redox conditions, radio-ionizating and cosmic conditions, solvent conditions etc., as well as in conditions simulating an ocean-boiling asteroid impact... Diverse molecular ecosystems could potentially have arisen in these physico-chemical specifications and we have to take them into account especially if the hereditary criteria are retained as mandatory in designing life.…”
Section: Marie-christine Maurelmentioning
confidence: 99%
“…Minerals and mineral surfaces, salt and crystals may help to stabilize macromolecules and monomers (Tehei et al, 2002;Corne´e et al, 2004;Ricardo et al, 2004). Purines and pyrimidines have been found in sediment cores from both ocean and lake basins, some dating back as far as 25 · 10 6 year, but they may be the result of contamination or decomposition under anhydrous conditions.…”
Section: Marie-christine Maurelmentioning
confidence: 99%
See 1 more Smart Citation